2005
DOI: 10.1103/physrevb.71.024202
|View full text |Cite
|
Sign up to set email alerts
|

Off-center phonon scattering sites inEu8Ga16Ge30andSr<

Abstract: We present a detailed extended x-ray absorption fine structure ͑EXAFS͒ analysis of the thermoelectric clathrates Eu 8 Ga 16 Ge 30 and Sr 8 Ga 16 Ge 30 , both of which have an unusually low thermal conductivity attributed to a "rattler" motion of the filler atoms Eu and Sr. The EXAFS results show that the Ga/ Ge lattice is quite stiff with a high correlated Debye temperature ϳ400 K. Eu is on-center in the site 1 cage but off-center ͑0.445± 0.020 Å͒ in the large cage called the Eu2 site. The results for Sr are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 37 publications
7
61
0
Order By: Relevance
“…Still, good arguments were made by the authors in terms of describing how off-center vibration does indeed help enhance the coupling between guest vibration modes and the framework phonons. 13,14 A second challenge to the TRR model is: can the shift from crystalline to glasslike behavior be explained solely by phonon scattering mechanisms within the framework, i.e., by interactions between phonons and charge carriers? This question was raised in a series of papers by Bentien et al 15,16,18 which we now discuss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, good arguments were made by the authors in terms of describing how off-center vibration does indeed help enhance the coupling between guest vibration modes and the framework phonons. 13,14 A second challenge to the TRR model is: can the shift from crystalline to glasslike behavior be explained solely by phonon scattering mechanisms within the framework, i.e., by interactions between phonons and charge carriers? This question was raised in a series of papers by Bentien et al 15,16,18 which we now discuss.…”
Section: Discussionmentioning
confidence: 99%
“…One proposes that the tunnelling states are not required, only an off-center vibration of the guest ions, 13,14 and another proposes that the guest ions don't play a major role at all at low temperatures, but rather it is the phonon scattering on charge carriers that leads to the glasslike behavior. 15,16,17,18 In this work we address the issue by performing single crystal x-ray diffraction (SCXRD), thermal conductivity κ(T ) and heat capacity C p (T ) experiments on Ba 8 Ga 16 Sn 30 (BGS) and Ba 8 Ga 16 Ge 30 (BGG) crystals, which have been tuned through the crystal growth process to display n-type or p-type majority charge carriers as a result of small imbalances in their Ga:Ge or Ga:Sn ratios.…”
Section: Fig 1: (Color Online)mentioning
confidence: 99%
“…The majority of previous works on type-I clathrates has focused on the low value and glass-like temperature dependence of κ L , whose origin is thought to be acoustic phonon scattering by "rattling" effects, i.e., low-energy guest vibrations. [22][23][24][25][27][28][29][30] Among type-I clathrates, Ba 8 In 16 Ge 30 shows one of the lower values of κ L = 0.9 W/m K at 300 K. 31 In this work, we report a partial control of the cage size of this compound by substituting Si and Sn for Ge, to clarify the relation between the free space available for the guest atom in the tetrakaidecahedron, its vibration energy, and the lattice thermal conductivity. …”
Section: -21mentioning
confidence: 99%
“…X-ray absorption near edge spectroscopy (XANES) and also susceptibility measurements, point to a predominant 2+ ions are subjected to a potential with four symmetric off-center energy minima. In these cages, it was found that the dynamical behavior of the Eu 2+ ions includes not only an off-center thermal activated rattling mode, but also quantum tunneling between the low temperature potential energy minima 19,20 . In this work, we report a non-trivial evolution of the X-band ESR spectra of EuT 4 Sb 12 (T = Ru, Os).…”
Section: +mentioning
confidence: 99%